An introduction to theoretical and computational aerodynamics - Moran, Jack (Dover Books on Aeronautical Engineering., 2003)
This concise and highly readable introduction to theoretical and computational aerodynamics integrates both classical and modern developments, focusing on applying methods to actual wing design. Designed for a junior- or senior-level course and as a resource for practicing engineers, it features 221 figures. 1984 edition.